Drone use in military and civilian application: risk to national security / Wardatul Hayat Adnan and Mohd Fadly Khamis - Adnan, Wardatul Hayat; Khamis, Mohd Fadly (Universiti Teknologi MARA, 2022)
Information travels through many different ways with the existence of the internet. Since then, the information has travelled faster than usual. Ensuring the safety of a country towards any threat through extensive analysis on the tactical communication warfare used by opponents. Therefore, the development of new technologies and tactics developed in today new modern information warfare cannot be neglected. The concept has increased tremendously since early 2019 from military use shifting to civilian application. Misuse of the drone technology will endanger the national security. Therefore, the present study aims to review the use of drones in military, and civilian application as well as to identify reasoning on its usage. It will later explain how the misuse of drone technology will affect the national security. Military drones used to collect information and act as a medium of communication in higher command control as well as terminating the opponents are found to be the modern information warfare among the users. Meanwhile, the commercial drone use among civilians fit the purpose of surveying land, buildings, entertainment, and creative industry. A Qualitative study approach used in a through secondary data (literature review) to suit the purpose of the present study. Reviews conducted using keywords search in Boolean concept. In addition, the review contents will further illustrate and explain the current use of drone among military and civilians and risk to our national security.